Diversidade genética de cladocera (Crustacea: Branchiopoda) do Sul de Minas Gerais, utilizando DNA Barcode como marcador molecular - Abreu, Cínthia Bruno De (2016)
Cladocerans are popularly known as water fleas, inhabit mainly freshwater aquatic environments and are considered good trophic indicators. These microcrustaceans have been used in basic and applied research, such as ecological, evolutionary and ecotoxicological studies. Morphological tools have been used to detect species richness of cladocerans from Minas Gerais, but given the difficulty of this morphological analysis, it is interesting to access this biodiversity by molecular tools as the DNA barcode. This molecular marker is based on a short segment of the mitochondrial gene cytochrome c oxidase subunit 1 (COI). It has been increasingly used in taxonomy, identification of cryptic species and diversity studies. In this context, we characterized the genetic diversity of Cladocera species from a point in the Furnas Hydroelectric Power Plant Resevoir and another in the Heliodora city (both in the south of Minas Gerais). This is the first molecular Cladocera inventory in Brazil, whose objective was to differentiate the Brazilian isolates of specimens from other countries, thus verifying taxonomic problems and cryptic species. We obtained sequences for 11 Cladocera species, distributed in Sididae, Daphnidae, Bosminidae and Chydoridae. The amplified fragments range from 493 to 659 base pairs, of which 90% were larger than 500 bp. Some of these COI sequences (for Bosmina freyi and Bosminopsis deitersi) represent the first molecular data in the world. We also found that the majority of Brazilian isolates are molecularly different from specimens from Mexico, Canada and Guatemala. For Daphnia laevis the genetic differences found between the Brazilian and Argentine isolates qualify them as members of the same taxonomic entity, reinforcing the concept of continental endemism. Besides the evaluation of diversity, with the determination of the COI for Ovalona kaingang (Cladocera: Chydoridae) we confirmed the morphological data, relocating the pulchella-group species to Ovalona, since the genetic differences between Ovalona and other species from the database were higher than 19.1%. Therefore, the use of DNA barcode was efficient to detect the genetic diversity of Cladocera specimens as a taxonomic tool. In the future our data can be applied to phylogenetic diversity studies, geographic distribution, biogeographic patterns and to assist in taxonomic revisions.